Family Background, Entrepreneurship Education, And Creativity In Supporting Entrepreneurship Intention - Cahyani, Rusnandari Retno; Riani, Asri Laksmi; Kurniadi, Edi; Paningrum, Destina (Asia Pacific Journal of Management and Education (APJME), 2018)
Family business has a key role in economic growth and labor. Entrepreneurship education(EE) is any activity that aims to inculcate the mindset or mindset about entrepreneurship, fostering the intention, attitude and competence of a person in developing his potential by realizing creative and innovative behavior. Objectives to be achieved in research are (1)to analyze the influence of family background variables on entrepreneurship intention. (2)Analyze the influence of entrepreneurship education from variable to entrepreneurship intention. (3) Analyze the influence of creativity variable on entrepreneurship intention. (4)To analyze the effect of family background variables, entrepreneurship education and creativity together on the intention of entrepreneurship. This research is a descriptive research using quantitative approach. The location of this research is at Sahid University of Surakarta with total of 100 respondents. Data collection used in this research is questionnaire, observation and literature. The results obtained that the three independent variables are family background, entrepreneurship education and creativity positively influences entrepreneurship intention. Hypothesis testing using t test shows that all independent variables have significant less than 0.05. Then through the F test known that the three independent variables proved to have a significant influence together on entrepreneurship intention. The authors suggest that future research is needed approaches in Entrepreneurship education for others college students or university.